The similar eye movement dysfunction between major depressive disorder, bipolar depression and bipolar mania. (21st October 2022) - Wang, Ying; Lyu, Hai-Long; Tian, Xiao-Han; Lang, Bing; Wang, Xiao-Yi; St Clair, David; Wu, Renrong; Zhao, Jingping
Abstract: Objective: To find eye movement characteristics in patients with affective disorders. Method: The demographic and clinical evaluation data of patients with major depressive disorder (MDD), bipolar disorder (BPD), and healthy control (HC) were collected. EyeLink 1000 eye tracker was used to collect eye movement data. Chi-squared test and independent sample t -test were used for demographics and clinical characteristics. The Mann–Whitney U -test was used to compare the eye movement variables among four groups, and the FDR method was used for multiple comparison correction. Pearson correlation analysis was used to analyse the relationship between clinical symptoms and eye movement variables. Results: Patients with affective disorders showed smaller saccade amplitude under free-viewing task, more fixations and saccades, shorter fixation duration, longer saccade duration under fixation stability and smooth pursuit tasks (all, p < 0.05) when compared to HC, but there was no significant difference in all eye movement variables among patients in the three groups. Also, all eye movement variables under the three paradigms had no significant correlation with clinical scale scores. Conclusion: Patients with major depression, bipolar depression and bipolar mania share similar eye movement dysfunction under free-viewing, fixation stability and smooth pursuit tasks.